(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Kefir is a probiotic-rich fermented milk product with numerous health benefits. This study investigates the impact of moringa leaf powder (MLP) fortification at different concentrations (0%, 3%, and 7%) on its proximate composition, viscosity, total plate count (TPC), pH, energy, dietary fibre, and sensory properties. Results showed that kefir fortified with 3% MLP had higher protein (7.42%) and ash (1.30%) than the control, while 7% MLP increased protein (7.73%) and ash (1.37%). Dietary fibre rose from 0.12% (control) to 0.36% (3% MLP) and 0.51% (7% MLP). Moisture decreased from 87.35% (control) to 85.67% (3% MLP) and 84.33% (7% MLP). Viscosity increased significantly, from 7.109 mPa (control) to 24.950 mPa (3% MLP) and 64.777 mPa (7% MLP). TPC of lactic acid bacteria increased from 9.13 Log10 CFU/ml (control) to 9.61 Log10 CFU/ml (7% MLP), indicating improved probiotic potential. The pH rose from 4.27 (control) to 4.43 (3% MLP) and 4.62 (7% MLP), while energy content increased to 61.53 kcal/100 g (3% MLP) and 64.78 kcal/100 g (7% MLP). Sensory evaluation showed that 3% MLP had the highest overall acceptability (7.2), with a smoother texture (6.8) and mild herbal flavour (6.5), while 7% MLP exhibited a coarser texture (5.4) and higher bitterness (5.1). A moderate MLP fortification (3%) improved kefir’s nutritional value while maintaining sensory appeal. This study highlights MLP’s potential as a functional ingredient in nutrient-dense dairy products.